2014
DOI: 10.1016/j.mvr.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Relative indexes of cutaneous blood perfusion measured by real-time laser Doppler imaging (LDI) in healthy volunteers

Abstract: We used real-time LDI to study regional variations in microcirculatory perfusion in healthy candidates to establish a new methodology for global perfusion body mapping that is based on intra-individual perfusion index ratios. Our study included 74 (37 female) healthy volunteers aged between 22 and 30 years (mean 24.49). Imaging was performed using a recent microcirculation-imaging camera (EasyLDI) for different body regions of each volunteer. The perfusion values were reported in Arbitrary Perfusion Units (APU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…Our study confirmed that blood flow in different cutaneous regions varied . Face and fingertips have higher perfusion values, especially eyelid and lips, which is consistent to the conclusion of Tur.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study confirmed that blood flow in different cutaneous regions varied . Face and fingertips have higher perfusion values, especially eyelid and lips, which is consistent to the conclusion of Tur.…”
Section: Discussionsupporting
confidence: 90%
“…There was also no significant correlation between skin perfusion values and BMI after adjustment for age and sex in our study, which agrees with S. Morteza's conclusion . Microcirculatory dysfunction has been proposed to be an additional mechanism relating obesity through insulin resistance, and reduced capillary blood flow may contribute to the development of insulin resistance in muscle and other organs …”
Section: Discussionsupporting
confidence: 89%
“…Baseline skin blood flow is highly variable and changes according to the body part . We recently extensively reviewed the mechanisms of tests used to challenge the skin .…”
Section: Which Dynamic Tests Are Commonly Used?mentioning
confidence: 99%
“…A special camera recorded 20,000 images per second to sample the frequency spectrum. These images will be analyzed and compressed, resulting in perfusion, concentration, and speed information of the monitored tissue (Seyed Jafari et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This study aimed to determine the applicability of LDI‐devices, as a contactless, non‐invasive and simple to use high speed camera, to visualize microcirculation in real‐time in the post‐operative monitoring of digital replantation, in comparison to traditional clinical evaluation and temperature‐monitoring. The advantages and disadvantages of these procedures are assessed (Seyed Jafari, Schawkat, Van De Ville, & Shafighi, ).…”
Section: Introductionmentioning
confidence: 99%